Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Guru Smk Gajah Mada Bandar Lampung - Yohanson A.K.; Lukmanul Hakim; Riyadini Riyan Utami; Aurelia Salsabila (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
This study aims to determine the effect of work environment and work motivation on teacher performance at SMK Gajah Mada Bandar Lampung. This type of research utilizes quantitative studies with associative methods. The results of the study of the results of data analysis and hypothesis testing have been carried out to increase the translation of the results of the study related to the factors that trigger the performance of teachers of SMK Gajah Mada Bandar Lampung, it can be drawn as a summary, namely. The physical work environment has an impact on performance. Work motivation has an impact on performance and the physical work environment and work motivation has an impact on the performance of SMK Gajah Mada Bandar Lampung teachers.